2010
DOI: 10.1016/j.ijgo.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of unsafe abortion in countries of Central Eastern Europe and Central Asia

Abstract: Despite permissive laws and a well-developed network of facilities, the incidence of unsafe abortion and the resulting maternal mortality is unacceptably high in Central and Eastern Europe and Central Asia, with one-quarter of all maternal deaths reported to occur as a consequence of abortion. Among the reasons that oblige women to submit themselves to risky procedures are new legislative barriers to accessing pregnancy termination, the unequal distribution of abortion services and healthcare providers, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Countries of the former Soviet Union, now referred to as the Newly Independent States, suffered during the Soviet-era from lack of access to modern contraception, and as a result continue to have among the high abortion rates in the world [1]. One study found about half of pregnancies in Eastern Europe and the Former Soviet Union were unintended, and that the vast majority of these pregnancies ended in induced abortion [2].…”
Section: Introductionmentioning
confidence: 99%
“…Countries of the former Soviet Union, now referred to as the Newly Independent States, suffered during the Soviet-era from lack of access to modern contraception, and as a result continue to have among the high abortion rates in the world [1]. One study found about half of pregnancies in Eastern Europe and the Former Soviet Union were unintended, and that the vast majority of these pregnancies ended in induced abortion [2].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors, including demographic characteristics, culture, religion, and socio-economic status, play an important part in the selection of modern contraceptive methods [1][2][3][4][5][6][7][8][9]. Globally, many women still rely on, and accept, the use of induced abortion as a means of fertility control [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, many women still rely on, and accept, the use of induced abortion as a means of fertility control [2][3][4]. Although the incidence of induced abortion has markedly decreased in Eastern Europe over the past decade, this region continues to have one of the highest rates in the world [2].…”
Section: Introductionmentioning
confidence: 99%
“…Poor socioeconomic status ,curettage done by unqualified persons, lack of specialist centres and doctors in rural areas, reluctance and hesitancy of both the parents family and abortionist, delayed referral due to unrecognized injury, these complications go unrecognized and lead to higher mortality and morbidity. 8,9 Late presentations have a more protracted stay and poorer outcome.…”
Section: Discussionmentioning
confidence: 99%